Sales, Profit and Financial Performance of Manufacturing Companies in Indonesia during Pandemic - Rasyid, Mohammad Kurniadi (Adpebi Science Series, 2022)
The purpose of this study was to determine the effect of the Covid-19 outbreak on sales growth and financial performance of companies specifically engaged in food production and household needs. Financial Performance is analyzed through the calculation of financial ratios which include liquidity ratios, activity ratios, solvency ratios and profitability ratios. The sample of this research is three large companies that have been listed on the Indonesia Stock Exchange (IDX), namely: Unilever, Indofood and Mayora. The data source used is secondary data which is on the site www.idx.co.id. The financial data used is derived from the company's financial statements per Quarter starting from Quarter 1 2019 to Quarter 1 2020. This study uses descriptive analysis. Data processing was performed using SPSS software to perform multiple regression tests. The results of the analysis show sales growth and profit growth at Unilever and Indofood during the pandemic were not greatly affected, but Mayora experienced a reduction. Profitability ratios and activity ratios decreased, liquidity ratios and solvency ratios experienced a slight improvement during the Covid-19 Pandemic for all sample companies.